Case Report: Incidental finding of Zinner syndrome in an asymptomatic 53-year-old Palestinian male - Abu-Hilal, Lila H.; Barghouthi, Duha I.; Njoum, Yumna; Obeid, Amal; Alshawwa, Khaled; AbuKeshek, Tawfiq; Maree, Mohammed (Frontiers in Urology, 2023)
Introduction: Zinner syndrome (ZS) is a rare condition characterized by a triad of seminal vesicle cyst (SVC), ipsilateral ejaculatory duct obstruction, and ipsilateral renal agenesis. The diagnosis is often delayed due to non-specific symptoms, such as lower urinary tract symptoms and infertility, typically appearing in the second and third decades of life. Case Presentation: We present the first published case of ZS in Palestine, involving a 53-year-old male patient who sought medical attention for right-sided hernia repair. Pre-operative imaging revealed a combination of findings, including a solitary left kidney with cysts, bilateral mild hydronephrosis, an enlarged prostate, suspicious soft tissue density, and abnormal lymph nodes. The diagnosis of ZS was confirmed through an abdominal ultrasound, identifying a dilated seminal vesicle and completing the criteria of ZS. Discussion: The typical for ZS is to present in late second decade of life with nonspecific urogenital symptoms and infertility, However, our patient’s incidental diagnosis during the preoperative evaluation of incisional hernia in a relatively old age with no previous complaints, the identification of a high aortic bifurcation at the level of the left kidney and a double Inferior Vena Cava (IVC) in this case of ZS represents novel and distinctive findings not commonly reported in previous cases. Conclusion: Our patient’s presentation and findings expand our understanding of the anatomical variations associated with ZS. This case report contributes to the advancement of knowledge in the field of ZS and provides valuable insights for future clinical management and research investigations.